Impact of traumatic injuries to the permanent teeth on the oral health-related quality of life in 12–14-year-old children - Cortes MIS , Marcenes W, Sheiham A. (Blackwell Synergy, 2002)
There are no data on the impacts on daily living of traumatic injuries to the permanent teeth. The aim of the present study was to assess the socio-dental impacts of untreated fractured anterior teeth in Brazilian schoolchildren.